Effect of inclusion of pitch-angle dependence on a simplified model of RF deposition in tokamak plasma. (1st May 2022) - Taylor, D M A; Mantsinen, M J; Gallart, D; Manyer, J; Sirén, P; ,
Abstract: Using the PION ICRH modelling code and comparisons against JET tokamak experiments, the effect of including pitch angle dependence within the RF diffusion operator on the fast ion particle distribution functions is quantified. It is found to be of greatest importance in cases of higher harmonic heating and lower heating ion mass, resulting in faster drop-off of the distribution's high energy tail. We see differences of several orders of magnitude in the high-energy range and significant non-linear alterations by several tens of percent to ion species power partition. ITER scenario operational parameters are also considered, and this improved treatment is shown to benefit anticipated ITER scenarios with second harmonic hydrogen heating, according to our predictions. PION's combination of benchmarked simplified wave physics and Fokker-Planck treatment offers modelling advantages. Since including the pitch angle dependence in the RF diffusion operator has not led to a significant increase in the required computing time when modelling different ICRF schemes in JET discharges, it has been made available within the production code.